Pengaruh Capital Intenisty, Perencanaan Pajak, Dan Risiko Bisnis Terhadap Nilai Perusahaan: (Studi Empiris pada Perusahaan Sektor Konsumen Primer di Bursa Efek Indonesia Tahun 2018-2022) - Sevhia Fransiska Trivena Br. Naibaho; Dian Widiyati (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
The study was conducted by analyzing the 2018-2022 annual financial reports of primary consumer companies listed on the Indonesia Stock Exchange. The sample used in this study consisted of 35 large consumer sector companies listed on the Indonesia Stock Exchange during the 2018-2022 period using a purposive sampling technique. The variables used in this study are capital intensity, tax planning, business risk as independent variables, and firm value as dependent variables. The research method uses the panel data regression method using EViews 13 Student Version Lite software. Based on the results of the study, the best model is the fixed effect model. The results of the study indicate that there is an influence of capital intensity, tax planning, and business risk on firm value simultaneously, there is an influence of capital intensity on firm value with a significant negative effect, tax planning on firm value is stated to have no significant effect and there is an influence of business risk on firm value with a significant positive effect.